(x+1)/2=(x+3)/3

Simple and best practice solution for (x+1)/2=(x+3)/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+1)/2=(x+3)/3 equation:



(x+1)/2=(x+3)/3
We move all terms to the left:
(x+1)/2-((x+3)/3)=0
We calculate fractions
x/()+(-((x+3)*2)/()=0
We calculate terms in parentheses: +(-((x+3)*2)/(), so:
-((x+3)*2)/(
We multiply all the terms by the denominator
-((x+3)*2)
We calculate terms in parentheses: -((x+3)*2), so:
(x+3)*2
We multiply parentheses
2x+6
Back to the equation:
-(2x+6)
We get rid of parentheses
-2x-6
Back to the equation:
+(-2x-6)
We get rid of parentheses
x/()-2x-6=0
We multiply all the terms by the denominator
x-2x*()-6*()=0
We add all the numbers together, and all the variables
x-2x*()=0

See similar equations:

| 1.5x-0.5x=10 | | -12-7-12-7=x | | 3/2m+1/5m=2 | | x/9+1/3=1/18 | | x/9+1/3=1/8 | | 12a^2+11a2=0 | | 2(n+2)=9(6-n) | | 11-4x=-7x+17 | | x/16+2X=33 | | 2(x-10)=-6+2 | | -13+7=x+9 | | 2(x-10)=6x+10 | | 7(2m-1)-(3/5)m=6/5(4-3m) | | (Xx2)+125=2059 | | 3r^2-3r+1=37 | | x^2-20x+181=0 | | 31-(2x+9)=2(x+6)+x | | 1+4x-8=0 | | 8a-(4a-3)=1 | | 12x-18+8x-12+x=180 | | 32=9/4x | | 42=x-19 | | 1/6x+3/2=-1/3 | | 6(x-6)+2=8(x+20-6 | | 3/11=x/x+9 | | (x-2)(x-5)=8 | | 1/4x=116 | | .2-1x+2.5=-3.6 | | a^2+(2a)^2=400 | | 13.5x=-7+94.5 | | 6x=19,5 | | 4y-3+y+33=7y+30-5y |

Equations solver categories